Art Neological Lexis and Visual Culturе - Nedyalkova, Nely (Media and Language, 2018)
The article attempts to introduce contemporary art vocabulary (120 words) in a neological way. In short, neologisms are viewed from different perspectives: postmodernist and post-postmodernist, philosophical, psycholinguistic, sociolinguistic, aesthetical, normative, pragmatic and in the visual culture plan. The new words are analysed both according to traditional classifications and also within the non-standard parallels ”linguistics – art criticism – visual culture” and the triad “linguistics – visual culture – architecture”. The material includes lexico-semantic notes on art neologisms: lexico-semantic mini-groups of nouns and adjectives. Different aspects are discussed, such as word-formation, style, punctuation, graphics and context. The author puts forward the idea that neologisms are not alien to intellectualism; in fact, they are a complement to intellectual systems. At the end of the paper, a mini-glossary of the commented neologisms is provided.